The Impact of Using Computer Simulation on Correcting Physical Misconceptions in the Subject of Periodic Motion among Eleventh Grade Students in the Sultanate of Oman - Amal R. Malkawi; Rashid J. Al Maamari (Sultan Qaboos University, 2016)
This study aimed to detect the impact of using computer simulation on correcting physical misconceptions in the subject of periodic motion among the eleventh grade students in the Sultanate of Oman. The researchers used a quasi-experimental approach and the study sample consisted of 128 of eleventh grade. Students were selected randomly in a deliberate manner from two schools, in the North Batinah Governorate. The students were distributed into two groups; experimental and control. The experimental group consisted from (65 students) and studied the scientific material related to the unit of periodic motion using computer simulation. The control group consisted of 63 students and studied the same scientific material by traditional method.The study found a diverse and wide series of misconceptions in the subject of periodic motion and revealed the inability of students to provide a true scientific explanation for many phenomena that are related to the periodic motion. The study also found significant statistical differences in correcting the misconceptions sample in the subject of periodic motion due to teaching methods in favor of the experimental group. The study didn't show statistically significant differences due to gender.